2018
DOI: 10.1111/tpj.14098
|View full text |Cite
|
Sign up to set email alerts
|

Immune receptor genes and pericentromeric transposons as targets of common epigenetic regulatory elements

Abstract: Pattern recognition receptors (PRR) and nucleotide-binding leucine-rich repeat proteins (NLR) are major components of the plant immune system responsible for pathogen detection. To date, the transcriptional regulation of PRR/NLR genes is poorly understood. Some PRR/NLR genes are affected by epigenetic changes of neighboring transposable elements (TEs) (cis regulation). We analyzed whether these genes can also respond to changes in the epigenetic marks of distal pericentromeric TEs (trans regulation). We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 70 publications
5
69
0
1
Order By: Relevance
“…Pericentromeric: chromosome regions that flank the centromere Interestingly, the majority of these defense genes were not targeted by NRPE1-and/or ROS1dependent DNA (de)methylation, suggesting that their responsiveness is trans-regulated by DNA methylation (81). More recently, Cambiagno and coworkers (24) reported that P. syringae infection of Arabidopsis results in both the transient expression of pericentromeric TEs and the accumulation of RdDM-related sRNAs that map to both TEs and defense genes. Although the TEs were resilenced over time, the complementary defense genes remained active (24).…”
Section: Py57ch23_tonmentioning
confidence: 99%
See 2 more Smart Citations
“…Pericentromeric: chromosome regions that flank the centromere Interestingly, the majority of these defense genes were not targeted by NRPE1-and/or ROS1dependent DNA (de)methylation, suggesting that their responsiveness is trans-regulated by DNA methylation (81). More recently, Cambiagno and coworkers (24) reported that P. syringae infection of Arabidopsis results in both the transient expression of pericentromeric TEs and the accumulation of RdDM-related sRNAs that map to both TEs and defense genes. Although the TEs were resilenced over time, the complementary defense genes remained active (24).…”
Section: Py57ch23_tonmentioning
confidence: 99%
“…More recently, Cambiagno and coworkers (24) reported that P. syringae infection of Arabidopsis results in both the transient expression of pericentromeric TEs and the accumulation of RdDM-related sRNAs that map to both TEs and defense genes. Although the TEs were resilenced over time, the complementary defense genes remained active (24). Cambiagno and coworkers proposed that this antagonistic response is caused by sRNA competition, whereby sRNAs are allocated away from the defense-related genes toward the TEs (24).…”
Section: Py57ch23_tonmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the detected TEs correspond to Helitron family. Indeed, researchers have identified both types of TEs associated with genetic and epigenetic variation located in proximity to disease resistance NBS-LRR genes (Kawakatsu et al ., 2016; Underwood et al ., 2017; Cambiagno et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing evidences of the impact that TEs have on the transcriptome on a given condition. For instance, TEs may have direct effects on genes, by providing them with new coding or regulatory sequences, an effect on the epigenetic status of the chromatin close to genes, and more subtle effects by imposing diverse evolutionary constraints to different chromosomal regions (Makarevitch et al, 2015;Vicient and Casacuberta, 2017;Cambiagno et al, 2018).…”
Section: Soybean Represents An Example Of a Thoroughly Annotated Tes mentioning
confidence: 99%